2007
DOI: 10.1021/bc0700741
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Mono- and Multimeric Targeted Radiopharmaceuticals Based on Novel Cyclen Ligands Coupled to Anti-MUC1 Aptamers for the Diagnostic Imaging and Targeted Radiotherapy of Cancer

Abstract: Targeted radiopharmaceuticals offer the possibility of improved tumor imaging and radiotherapy, with reduced side effects. A variety of monoclonal antibodies and antibody fragments have previously been successfully radiolabeled and used in diagnostic imaging and targeted radiotherapy of cancer. Many such antibodies have been shown to recognize the well-characterized MUC1 tumor marker and have recently been in clinical trials. Furthermore, a number of chelators have been synthesized and are currently used as ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 37 publications
1
80
0
1
Order By: Relevance
“…In addition, Muc1 is an attractive target, as its overexpression has been associated with various types of cancer and its distribution pattern changes on the cell surface (82,83). DNA aptamers directed against Muc1 (AptA and AptB) were identified in 2006 (84) and have since been implemented in ex vivo imaging and radiotherapy (85). In subsequent studies, when such an DNA aptamer was coupled to the light-activated photodynamic therapy agent chlorine e6, it specifically delivered chlorine e6 into epithelial cancer cells, with a significant enhancement in efficiency (>500-fold increase) compared to that of the drug alone, and achieved cancer-specific cytotoxicity (86).…”
Section: Clinical Applications Of Aptamers In Cancermentioning
confidence: 99%
“…In addition, Muc1 is an attractive target, as its overexpression has been associated with various types of cancer and its distribution pattern changes on the cell surface (82,83). DNA aptamers directed against Muc1 (AptA and AptB) were identified in 2006 (84) and have since been implemented in ex vivo imaging and radiotherapy (85). In subsequent studies, when such an DNA aptamer was coupled to the light-activated photodynamic therapy agent chlorine e6, it specifically delivered chlorine e6 into epithelial cancer cells, with a significant enhancement in efficiency (>500-fold increase) compared to that of the drug alone, and achieved cancer-specific cytotoxicity (86).…”
Section: Clinical Applications Of Aptamers In Cancermentioning
confidence: 99%
“…The tumor-to-blood ratio was > 50 three hours post injection, and > 180 after 16 h, while the control antibody required 40 h for a T/B ratio of 5. An anti-MUC1 aptamer was labeled with technetium complexed with four different bifunctional chelators bearing carboxylic acid bioconjugatable functionalities (Borbas et al, 2007). The complexes were formed by reduction of the pertechnetate with sodium borohydride, followed by treatment with a solution of the chelator.…”
Section: Aptamer Labeling With Radiometalsmentioning
confidence: 99%
“…Aptamers offer low immunogeniciy, good tumour penetration, rapid uptake and fast systemic clearance, which favour their application as effective vehicles for cytotoxic agents or 4 radioisotopes [15][16][17][18]. To date few examples of radiolabelling of aptamers can be found in literature showing that aptamers can be used as targeting agents in imaging and in radio-therapy [19][20][21]. With regards to the potential efficacy of aptamers as targeted radiopharmaceuticals in cancer therapy, we have previously shown that aptamers have improved tumour penetration, when compared with antibodies [21].…”
Section: Introductionmentioning
confidence: 99%
“…To date few examples of radiolabelling of aptamers can be found in literature showing that aptamers can be used as targeting agents in imaging and in radio-therapy [19][20][21]. With regards to the potential efficacy of aptamers as targeted radiopharmaceuticals in cancer therapy, we have previously shown that aptamers have improved tumour penetration, when compared with antibodies [21]. It is speculated that radiolabelled aptamers would have great potential as imaging agents, given that the majority of the aptamer not bound to the tumour is cleared rapidly from the system.…”
Section: Introductionmentioning
confidence: 99%